Collaborative Governance Dalam Perlindungan Anak di Kota Batam Tahun 2020 - Raja Indriani Fajrianti; Adji Suradji Muhammad; Edy Akhyari (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2022)
The problem of child abuse is a problem that occurs every year. For this reason, the problem of child abuse cannot be handled by one institution only so that the government and other institutions collaborate. This research aims to find out the processes and factors inhibiting Collaborative Governance in child protection at Batam city in 2020. This research uses a descriptive qualitative approach with the data sources used are primary and secondary data, where the data collection uses observation, interview and documentation techniques. Data that has been analyzed using measures including data reduction, presentation of data and withdrawal of conclusions. In this Collaborative Governance study, researchers used the theory of Ansell and Gash. The results of this study show that the collaborative process runs quite well by looking at the indicators of face-to-face dialogue conducted with coordination meetings that are quite often carried out by actors, on indicators of trust building with the intensity of communication established, on indicators of commitment to the process with the interrelationship of tasks and functions of actors, on indicators of share understanding with responsibility with their respective tasks and functions, and on indicators of Intermediated Outcomes results facilitate in child protection, the increase in the intensity of communication, and changes in the behavior of government agencies. But the inhibiting factors in the protection of children are still lack of socialization, lack of community participation, and difficulty getting information.